Persepsi Remaja Tentang HIV/AIDS Pada Organisasi Berbasis Komunitas (OBK) di Kota Makassar Tahun 2020 - Aulia Apriliani; A. Rizki Amelia AP; Rusyidi, Arni Rizqiani (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Acquired Immune Deficiency Syndrome (AIDS) is interpreted as a symptom or disease caused by decreased immunity due to infection with Human Immunodeficiency Virus (HIV). The highest HIV/AIDS sufferers by age in South Sulawesi Province in 2019 are aged 15-29 years and Makassar City is the city with the highest number of sufferers HIV/AIDS as many as 430 people. The purpose of this study was to determine adolescent perceptions about HIV/AIDS in Community Based Organizations (OBK) in Makassar City in 2020. The type of research used was qualitative with a phenomenological approach. The informants in this study consisted of key informants, supporting informants, and ordinary informants who done with the snowball sampling method. From the results of the study it was found that adolescents who are members of the Makassar State University MAPHAN UKM show the perception of the vulnerability of girls knowing the risk of disease. The perception of seriousness shows that adolescents know the seriousness of an individual's illness by explaining and determining the impact of the risks and conditions. Perception Encouragement to act shows that adolescents already know the urge to make prevention efforts to the community by explaining and providing awareness to the community. Perception of benefits shows that adolescents already know the benefits of HIV/AIDS prevention efforts by determining the actions taken to prevent disease and the perceived benefits. Perception of barriers shows that adolescents can explain the obstacles in carrying out efforts to prevent HIV/AIDS through the impact that will occur when not making these efforts. Adolescents can explain the perception of vulnerability to the risk of HIV/AIDS, seriousness in dealing with HIV/AIDS, encouragement to act in efforts to prevent HIV/AIDS, and the benefits of HIV/AIDS prevention efforts and perceived obstacles when making these efforts.